Formula pada Tradisi Togal - Rudi Tawari (Tekstual, 2018)
This article discuss the element of the formula as the oral characteristics on each of the oraltradition, including togal.Ã‚Â  Formula that reported by Albert Lord be a reference to analyzeoral creation in togal. The formula is the element of the language used by chanter or singerin making easy their syair and pantun. The Singer composes his syair and pantun when doingtogal not prepared by written. In order to, this writing will describe the use of the formula inthe oral creation that used by the singer.